Cognitive Behavior Therapy in The School Setting: A Case Study of A Nine Year Old Anxious Boy with Extreme Blushing - C. Jellesma, Francine (Journal of Depression And Therapy, 2017)
Within the field of school psychology there is a gap between research and practice, caused by difficulties in translating the programs from research to the realities of the school setting. Illustrations of real-life cases may help school psychologists gain insight into the application of interventions. The purpose of this study was to describe an example of small group cognitive behavior therapy in the school setting. It concerned test anxiety with extreme blushing. A single subject case study of a nine year old Dutch boy was described. Interviews, observations and questionnaires were used for evaluation, as well as a standard national achievement test. The results indicate that the test anxiety and blushing decreased and on the achievement test three years later, performance was good.  As it concerns a case study, the results are discussed tentatively. It was concluded that the intervention was successful without alterations to the program. This study provides an illustration of research put into practice.
Keywords: blush; CBT; case study; school intervention; social phobia